Comparison of Slavonian forest by Josip Kozarac and Adolf Waldinger - Bilić, Anica (Poznańskie Studia Slawistyczne, 2012)
In this article we shall compare the literary work Slavonian forest by Josip Kozarac with Adolf Waldinger’s oil painting Slavonian forest, including his drawings and pictures of a Slavonian forest and forest details. Comparison is made primarily on the basis of their resemblance. Not only do both of these works have the same inspiration and structure, but in terms of content they also elaborate the motifs andthemes of the forest landscape, leaning toward realistic formation, and both represent works of anthological value. In other words, Waldinger’s Slavonian forest is one of his best works and an excellent work in the field of Croatian forest painting, while Kozarac’s work finds itself at the anthological peak of Croatian descriptive literature.